Catalog of magnetic white dwarfs with hydrogen dominated atmospheres - Amorim, Larissa L.; Kepler, S. O.; Külebi, Baybars; Jordan, Stefan; Romero, A. D. (The astrophysical journal, 2023)
White dwarfs are excellent research laboratories as they reach temperatures, pressures, and magnetic fields that are unattainable on Earth. To better understand how these three physical parameters interact with each other and with other stellar features, we determined the magnetic field strength for a total of 804 hydrogen-rich white dwarfs (WDs) of which 287 are not in the literature. We fitted the spectra observed with the Sloan Digital Sky Survey using atmospheric models that consider the Zeeman effect due to the magnetic field at each point in the stellar disk. Comparing magnetic and nonmagnetic WDs, the literature already shows that the magnetic ones have on average higher mass than the nonmagnetic. In addition to that, magnetic fields are more common in cooler WDs than in hotter WDs. In consonance, we found that those with higher magnetic field strengths tend to have higher masses, and lower temperatures, for which models indicate the crystallization process has already started. This reinforces the hypothesis that the field is being generated and/or amplified in the cooling process of the white dwarf. Our sample constitutes the largest number of white dwarfs with determined magnetic fields to date.